PENDAMPINGAN TATA KELOLA KEUANGAN DALAM PENERAPAN LAPORAN LABA RUGI BAGI UMKM BAIM CELL: Financial Governance Assistance In The Implementation Of Profit And Loss Reports For Baim Cell Msmes - Widjanarko, Widjanarko; Yohanes ALS, Dewa Putu; Setiawan, Indra; Kristantini, Rr. Aryanti; Amalia, Fauziah; Marselina, Marselina; Anatria, Dinda; Papa, Yohanes Aprilianus; Damayanty, Prisila (PUAN INDONESIA, 2024)
The aim of this activity is to increase knowledge, skills and convenience for Baim Cell MSME entrepreneurs located in Beji, Depok. To manage finances in the form of reports. The techniques developed in service activities are in accordance with the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) for Baim Cell MSMEs who are able to apply simple bookkeeping for their business and are able to make financial reports independently. The data collection method used is qualitative, namely by carrying out several stages, including surveys, interviews, observation and documentation. From the interviews conducted, it can be seen that various main problems faced by the owners of Baim Cell MSMEs are related to the limited knowledge they have in managing their business regarding the preparation of financial reports. This makes it difficult for productive businesses to develop properly due to the inability to prepare financial reports which are a requirement for obtaining loans from banks or financial institutions. Therefore, by providing assistance activities regarding the preparation of financial reports for MSMEs that we carry out, we can provide insight, knowledge, skills and convenience for business actors to understand the preparation of financial reports and can directly apply them to the preparation of their business financial reports. The results of this training show that it turns out that BAIM CELL with initial capital of Rp. 48,000,300 turns out the net profit in a year is Rp. 39,940,300,-